The role of argumentation in critical thinking and epistemic writing in Biology and History: An approach from the social representations of teachers (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
The development of argumentation in the process of academic literacy is particularly important because scientific knowledge is essentially argumentative (Serrano y Villalobos, Niveles discursivos). For this reason, the purpose of this research is to elicit social representations about teaching and learning of argumentation from the discourse of teachers in a program of Biology and History, as well as to generate an explanatory model for this phenomenon. The data collection instrument used was an interview to teachers in both disciplines, and the data was analyzed using content analysis, a technique that seeks to develop replicable and valid inference that can be applied to a given context (Krippendorff, 1997).
Keywords: Argumentation; Academic writing; Social representations; Bachelor’s degree in Biology; Bachelor’s degree in History